Ethnomathematical Exploration of the Kelana Mask Dance in Cirebon, Indonesia: Geometric Concepts and Cultural Integration - Agni Rahima; Inah Sakinah; Almarsharen Pratiwi; Aghni Fatimatul Zahra; Subatul Ulum; Arif Muchyidin (MASI Mandiri Edukasi, 2026)
Geometry learning is often perceived as abstract and disconnected from students’ lived experiences; therefore, this study aims to explore the potential of the Gegesik-style Kelana Mask Dance (Cirebon) as a contextual medium for mathematics learning through an ethnomathematics approach. The study employed a descriptive qualitative approach with an ethnographic design, collecting data through a literature review, participant observation, and analysis of performance documentation (videos), systematic notes on movement structures and floor patterns, and interviews with dancers/artists to strengthen the interpretation of movement meanings. The findings indicate that the choreography of the Kelana Mask Dance embodies fundamental mathematical—particularly geometric—concepts such as angles, lines, rotation, symmetry, and plane figures; its floor patterns display geometric forms (e.g., circles, triangles, and straight lines), while directional changes and turns produce angles and symmetry that can be leveraged as learning contexts. In addition, the symbolism embedded in movements and dance properties enriches learning by linking mathematical ideas with cultural values. In conclusion, the Kelana Mask Dance has strong potential as an engaging, contextual resource for teaching geometry while also supporting the preservation of local culture and strengthening students’ cultural identity.